Aspek Hukum Impor Pakaian Bekas Berdasarkan Peraturan Perundang-Undangan - Yanuar Ika Safitri (Jurist-Diction, 2023)
Abstract In Indonesia, several laws and regulations concerning the prohibition on the import of used clothing are regulated in Law No. 8 of 1999 concerning Consumer Protection. 7 of 2014 concerning Trade, Regulation of the Minister of Trade No. 12 of 2020 also classifies used clothing as prohibited from being imported. However, there is one rule that there is a conflict of norms between the Regulation of the Minister of Trade No. 12 of 2020 concerning Goods Prohibited from Importing by Regulation of the Minister of Finance No. 6/PMK.10/2017 concerning Determination of Goods Classification and Loading. Based on the analysis, it can be concluded that in accordance with the legal principle of lex superior derogate legi inferior which is Regulation of the Minister of Trade No. 12 of 2020 whose powers are under Law no. 7 of 2014 prioritizes policies and the stipulation of criminal provisions against parties importing used clothing. Keywords: Import, Legal Liability, Used Clothing, Customs   Abstrak  Di Indonesia beberapa peraturan perundang-undangan tentang larangan impor pakaian bekas diatur pada Undang-Undang No.8 Tahun 1999 Tentang Perlindungan Konsumen  Di dalam Undang-Undang No. 7 Tahun 2014 Tentang Perdagangan, Peraturan Menteri Perdagangan No. 12 Tahun 2020 juga mengklasifikasikan pakaian bekas dilarang diimpor. Namun, ada salah satu aturan yang terdapat adanya konflik norma antara Peraturan Menteri Perdagangan No. 12 Tahun 2020 Tentang Barang Dilarang Impor dengan Peraturan Menteri Keuangan No. 6/PMK.10/2017 Tentang Penetapan Klasifikasi Barang dan Pembebanan. Berdasarkan analisa dapat disimpulkan bahwa sesuai dengan asas hukum lex superior derogate legi inferior yang mana Peraturan Menteri Perdagangan No. 12 Tahun 2020 yang kekuatannya dibawah Undang-Undang No. 7 Tahun 2014 lebih diutamakan kebijakan dan penetapan ketentuan pidana terhadap pihak yang melakukan impor pakaian bekas. Kata Kunci: Impor, Pertanggungjawaban Hukum, Pakaian Bekas, Kepabeanan